2011
DOI: 10.3892/mmr.2011.621
|View full text |Cite
|
Sign up to set email alerts
|

hsa-miR-96 up-regulates MAP4K1 and IRS1 and may function as a promising diagnostic marker in human bladder urothelial carcinomas

Abstract: Abstract. Numerous microRNAs (miRNAs) play crucial roles in cancer development. In this study, we report that hsa-miR-96 is expressed at higher levels in human bladder urothelial carcinomas compared to normal tissues. We found that hsa-miR-96 increased invasion and differentiation of human bladder T24 cells and promoted their growth. Down-regulation of hsa-miR-96 significantly affected the phenotype of bladder cancer T24 cells. The mRNA and protein levels of insulin receptor substrate 1 (IRS1) and MAP4K1 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 19 publications
1
41
0
2
Order By: Relevance
“…Moreover, the inhibitory effect on metastasis in hepatoma carcinoma cells, induced by the suppression of miR-96 [107], was reported as being associated with the inhibition of EFNA5 expression by miR-96-targeting [85]. Similar findings have been reported in case of gastric, bladder, and breast cancers [3, 7, 83, 108]. With regard to miR-182, Huynh et al reported significant suppression of invasive growth tendency and metastasis by suppressing miR-182 in vivo [109].…”
Section: Resultsmentioning
confidence: 55%
“…Moreover, the inhibitory effect on metastasis in hepatoma carcinoma cells, induced by the suppression of miR-96 [107], was reported as being associated with the inhibition of EFNA5 expression by miR-96-targeting [85]. Similar findings have been reported in case of gastric, bladder, and breast cancers [3, 7, 83, 108]. With regard to miR-182, Huynh et al reported significant suppression of invasive growth tendency and metastasis by suppressing miR-182 in vivo [109].…”
Section: Resultsmentioning
confidence: 55%
“…miR-96 was identified as the most significantly up-regulated miR, and miR-490-5p was the most significantly down-regulated miR. Wang et al confirmed increased expression of miR-96 in BC compared with normal tissue and demonstrated that this miR species increased cellular proliferation and invasion in the human BC cell line T24, possibly through induction of IRS1, a protein involved in insulin signaling, and MAP4K1, which belongs to the STE/Ser/Thr protein kinase family and mediates growth regulation and environmental stress response [26]. …”
Section: Resultsmentioning
confidence: 99%
“…In our study, we used the Hyaluronoglucosaminidase 1 gene as a starting point to generate a list of regulatory genes, in a ranking order of highest prediction, using relevant data bases. In addition, we selected lncRNA and miRNAs which were previously published in BC [9][10][11] and were reported to target HYAL1. Then, we performed pathway enrichment analysis and multiple sequence alignment to explore the intersected signaling pathways and their evolutionary relationship.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, associations between BC and several biomarkers such as lncRNA-UCA1 [9], miR-210 [10], miR-96 [11], miRNA-220, or Hyaluronoglucosaminidase 1 [12] were identified.…”
Section: Introductionmentioning
confidence: 99%